ANALISIS STRATEGI PEMASARAN PRODUK MIKADA DALAM MENINGKATKAN VOLUME PENJUALAN OLEH KELOMPOK USAHA PEREMPUAN “NADOLI NASINTUVU” DI DESA DAMPAL KECAMATAN SIRENJA - Nur Wanita; Arifka Indah; Rizki Amalia (Musawa: Journal for Gender Studies, 2023)
This study aims to analyze the marketing strategy of MIKADA products in increasing sales volume carried out by the women's business group "Nadoli Nasintuvu" in Dampal village, Sirenja District, Donggala Regency. The informant in this study was coordinator and head of business group Nadoli Nasintuvu and several consumers/buyers of MIKADA products. This study used a qualitative approach, where data collection techniques were obtained through observation, interviews, and ductumeation. The results showed that to increase sales volume, the marketing strategy carried out by the women's business group "Nadoli Nasintuvu" includes a labeling product strategy, highlighting product quality and using new packaging, pricing strategy, by setting prices according to operational costs incurred, place strategy, namely serving purchases at production houses, marketing in the local market and establishing partnerships with the Sikola Mombine Foundation to Marketing, while the promotion strategies used include advertising through the distribution of brochures, personal sales and publicity.